Triptofano para leitões e sua relação com a lisina na fase inicial - Pasquetti, Tiago Junior (2014)
Four experiments were carried out. In the first experiment it was aimed to evaluate the effect of oral Tryptophan (Trp) supplementation on the concentration of serotonin (5-HT) and 5-Hydroxyindoleacetic acid (5-HIAA); on performance of piglets in suckling phase (from 14 to 21 days old) and nursery phase (from 21 to 22 and from 21 to 56 days old); and on normal and aggressive behavior of piglets under social stress in the first day after weaning. Piglets were allotted in two experimental diets, a test diet, containing Trp four times above the requirements, and a control diet, containing Alanine (Ala) and glucose. It was concluded that Trp supplementation in suckling phase, increases the concentration of serotonin and 5-hydroxyindoleacetic acid in the hypothalamus of piglets and do not affect neither the performance in the suckling phase nor the aggressive behavior in the first day after weaning. Trp increases the frequency of visits to the feeders in the first day after weaning and improves feed conversion ratio of piglets in the first week after weaning. In experiment II, it was aimed to determine the standardized ileal digestibility of amino acids in the basal diet (BD) with the lowest Trp (0.150%) and Lys (0.900%) levels. For collection of ileal digesta, a total of 10 crossbred barrows were used, with an average initial weight of 21.5±1.57 kg. The ileal digestible standardized levels of Trp and Lys were 0.155 and 0.972%, respectively, which were considered in diet formulation for the performance assays (III and IV). The performance assays were performed in order to determine the optimum levels, the requirements in g/day, as well as the ideal ratio between digestible Trp and Lys levels. In Experiments III and IV, 64 barrows (15±1.63 kg) and 64 gilts (15.04±1.44 kg) were used, respectively, which were allotted in a randomized block design (RBD), with 16 treatments and four replications in a factorial scheme 4x4 (four levels of digestible Trp: 0.155, 0.185, 0.215, 0.245% and four levels of digestible Lys: 0.972, 1.112, 1.252 and 1.392%). At the end of the trials, performance, Longissimus dorsi depth (LDD), backfat thickness (BT) and blood parameters were measured. In additionally, body temperature (back, head, tympanum and recto) was measured. In the experiment three, the final body weight (FBW), average daily feed intake (ADFI) and average daily gain (ADG) increased linearly (P<0.05) with increasing levels of digestible Trp. A quadratic effect of Trp and Lys levels on feed conversion ratio (FCR) was observed, which were estimated the optimal levels of digestible Trp and Lys at 0.210% and 1.198%, respectively, resulting in a digestible Trp:Lys ratio of 17.5:100. Quadratic effect of Trp (P=0.021) and Lys (0.026) levels were noted on the LDD, in which the optimal levels of Trp and Lys were 0.208% and 1.136%, respectively, resulting in a digestible Trp:lys ratio of 18.3:100. Based on FCR, it was concluded that digestible Trp and Lys requirements for barrows are 0.210% and 1.198%, respectively, which corresponds in a ratio of 17.5:100. In experiment IV (females), a quadratic effect (P=0.038) of digestible Trp levels on the FBW and ADG was observed, while the ADFI increased linearly (P=0.005) with increasing levels of digestible Trp. For the FBW and ADG, 0.225 and 0.224% of digestible Trp were estimated, respectively. An interaction between digestible Trp and Lys levels was observed for FCR (P=0,007), which increased according to the levels of these amino acids, and reduced in the largest levels of Trp and Lys. The BT increased linearly (P=0.021) according to the digestible Trp levels. There was a quadratic effect (P=0.034) of digestible Trp levels on the LDD, in which the optimal level was estimated at 0.205%. Based on the ADG, it was concluded that the optimum level of digestible Trp for gilts, from 15 to 30 kg of body weight, is 0.224%, which corresponds to 2.99 g/day.